Physiological Adjustment of Arterial Blood Gases and Bicarbonate ION During Pregnancy in Human (Bangladesh Journal of Physiology and Pharmacology, 2010)
In the present study the partial pressure of oxygen (PaO2), carbon dioxide (PaCO2) and bicarbonate ion (HCO3-) in arterial blood were estimated in 32 women in Dhaka city. For this purpose a total of 32 women subjects with age ranged from 25 years to 35 years without any recent history of respiratory diseases were selected. Of those, 8 healthy non-pregnant women were included as control and 24 normal pregnant women as experimental group. The PaO2, PaCO2 and HCO3- were estimated during the first, second and third trimester by using 'easy blood gas auto analyzer'. The PaO2 was significantly higher during entire pregnancy period. However, the PaCO2 and HCO3- were significantly lower in first, second and third trimester of pregnant women than that of non-pregnant women. There were no statistically significant difference of PaO2, PaCO2 and HCO3- ion among first trimester, second trimester and third trimester. The progressively increased PaO2, decreased PaCO2 and HCO3- ion throughout the pregnancy is possibly due to the effect of progesterone causing hyperventilation. DOI: 10.3329/bjpp.v23i1.5724Bangladesh J Physiol Pharmacol 2007; 23(1&2) : 10-12